Communication about Congenital Adrenal Hyperplasia: Perspective of Filipino Families. Issue 4 (10th November 2016) - Abad, Peter James B.; Anonuevo, Cora A.; Daack‐Hirsch, Sandra; Abad, Lorna R.; Padilla, Carmencita D.; Laurino, Mercy Y.
Abstract: Congenital adrenal hyperplasia (CAH), like other genetic conditions, is a relational disease from both the biological and psychosocial perspectives since the diagnosis gives rise to a variety of health, reproductive, and psychosocial implications. It is in these contexts that family communication of genetic information is important to study. Hence, this research aimed to explore genetic information communication in Filipino families affected with CAH. Using a qualitative descriptive design, families with a child affected with CAH were recruited through the CAH parent support group and were interviewed. Semi‐structured interviews explored flow and content of genetic information communicated, the meanings the families attach to the communicated information, and the motivating and hindering factors in communication. Thematic analysis was used to analyze the findings. A total of five families participated, which included 11 individuals. Findings revealed that the diagnosis of CAH is not kept secret and it is openly shared with the family. The decision to communicate is influenced by several factors including the family's desire to seek further information about their family history. Initially, the focus of the communicated information is on the health implications and while communication about genetics occurs, this is almost always confined to the immediate family. The mother and grandmother serve as primary communicators in the family. The families have limited understanding of CAH especially its genetic implications including recurrence risk and carrier status. The findings can guide genetic counselors in supporting families in communicating information about CAH with the rest of the family.